Yayasan UMPSA reaches out to Bentong community, donates RM200,000 for Early Education Assistance and Excellence Incentive - Mimi Rabita, Abd Wahit (UMPSA, 2024)
BENTONG, 29 June 2024 - Yayasan UMPSA presented donations to ten families consisting of single mothers and families in need around Bentong in an effort to reach out and support the local community.